1968
DOI: 10.1002/aja.1001230206
|View full text |Cite
|
Sign up to set email alerts
|

The innervation of the bone marrow in laboratory animals

Abstract: The nerve pattern of the bone marrow of the monkey, rabbit, rat and mouse was studied in serial sections specially stained to demonstrate myelinated and nonmyelinated nerve fibers. Features that are common to the different species studied were found in the bone marrow of the femur of the rat in a simple arrangement.A scheme is proposed based on thirteen photomicrographs demonstrating the nerve pattern of the bone marrow and the relation of the nerve fibers with the arterial tree, the sinusoids and the blood fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(67 citation statements)
references
References 1 publication
4
63
0
Order By: Relevance
“…11 Studies in animal models showed the presence of sensory and autonomic nerves in the bone marrow as a morphologic correlate of a possible neural regulation of hematopoiesis. [12][13][14] However, the idea that neuromediators might directly influence hematopoietic progenitors is controversially discussed. [15][16][17][18][19] Recently, several investigators described partly overlapping genetic programs of hematopoietic and neuropoietic cells in mice.…”
Section: Introductionmentioning
confidence: 99%
“…11 Studies in animal models showed the presence of sensory and autonomic nerves in the bone marrow as a morphologic correlate of a possible neural regulation of hematopoiesis. [12][13][14] However, the idea that neuromediators might directly influence hematopoietic progenitors is controversially discussed. [15][16][17][18][19] Recently, several investigators described partly overlapping genetic programs of hematopoietic and neuropoietic cells in mice.…”
Section: Introductionmentioning
confidence: 99%
“…They determined that sympathetic nerves were distributed to the blood vessels and that afferent fibers were functionally related to the vessels, although some afferent fibers appeared to terminate in the marrow parenchyma. Calvo [1968], using a combination of silver techniques and connective tissue stains, studied the distribution of the nerves to the bone marrow of several laboratory animals. He described a rather abundant innervation of the marrow parenchyma and the walls of the venous sinusoids.…”
Section: Introductionmentioning
confidence: 99%
“…The SNS consists of adrenergic nerve fibers that exit the spinal cord to form para-spinal ganglia that innervate peripheral organs, including all primary and secondary lymphoid tissues (3)(4)(5). Studies of splenic architecture identified adrenergic nerve fibers in the capsule, traberculae, and white pulp (6).…”
mentioning
confidence: 99%